Unlocking Innovation through Leadership: The Interplay of Work-Life Balance and Flexibility - Made Ermawan Yoga Antara; Ida Ayu Oka Martini (Universitas Warmadewa, 2025)
This study contributes to supporting Balinese endek weaving SMEs to increase their competitiveness because the existence of SMEs is very important as a driver of the regional economy and job creation. This study examines the role of work-life balance and flexible work arrangement in increasing the influence of leadership on innovative work behavior. The study was conducted at an endek weaving SME in Klungkung Regency, Bali Province. The population of the study was employees of the endek weaving SME with a sample of 311 people determined based on proportional random sampling techniques and the Slovin formula. The data collection method was a survey using a questionnaire and data analysis using the PLS-SEM method via SmartPLS 3 programs which went through 3 stages: outer model analysis, inner model measurement, and the last stage was testing the research hypothesis. The results of the study showed a mediating role of work-life balance in increasing innovative work behavior. Flexible work arrangement was also able to moderate the relationship between democratic leadership and innovative work behavior. The results of this study serve as a reference for leaders of Balinese endek weaving SMEs in improving decision-making skills so that the productivity of employees of endek weaving SMEs in Klungkung Regency becomes better.